Brooklyn Bridge : a novel - Hesse, Karen (Feiwel and Friends, 2008)
Fourteen-year-old Joseph Michtom's life takes a dramatic turn when, in 1903 Brooklyn, his parents turn their apartment into a factory for making teddy bears; and Joseph wonders whether he will ever see the glitter of Coney Island.